"I can't remember the last time I was comfortable about being home": lived experience perspectives on thriving following homelessness. Issue 1 (31st December 2023) - Marshall, Carrie Anne; Phillips, Brooke; Holmes, Julia; Todd, Eric; Hill, River; Panter, George; Easton, Corinna; Landry, Terry; Collins, Sarah; Greening, Tom; O'Brien, Ashley; Jastak, Marlo; et al.
ABSTRACT: Purpose: Strategies for preventing and ending homelessness are frequently measured by their effectiveness on indices of tenancy sustainment. To shift this narrative, we conducted research to identify what is needed to "thrive" following homelessness from the perspectives of persons with lived experience in Ontario, Canada. Methods: Conducted in the context of a community-based participatory research study aimed at informing the development of intervention strategies, we interviewed 46 persons living with mental illness and/or substance use disorder [ n  = 25 (54.3%) unhoused; n  = 21 (45.7%) housed following homelessness] using qualitative interviews. A subsample of 14 participants agreed to engage in photovoice interviews. We analysed these data abductively using thematic analysis informed by health equity and social justice. Results: Participants described experiences of "living in a state of lack" following homelessness. This essence was expressed through four themes: 1) housing as part one of the journey to home; 2) finding and keeping "my people"; 3) meaningful activity as critical for thriving following homelessness; and 4) struggling to access mental health supports in the context of challenging circumstances. Conclusions: Individuals struggle to thrive following homelessness in the context of insufficient resources. There is a need to build on existing interventions to address outcomes beyond tenancy sustainment.